The isolated electron: De Broglie’s hidden thermodynamics, SU(2) quantum Yang-Mills theory, and a strongly perturbed BPS monopole - Hofmann, Ralf (Entropy, 2017)
Based on a recent numerical simulation of the temporal evolution of a spherically perturbed BPS monopole, SU(2) Yang-Mills thermodynamics, Louis de Broglie’s deliberations on the disparate Lorentz transformations of the frequency of an internal “clock” on one hand and the associated quantum energy on the other hand, and postulating that the electron is represented by a figure-eight shaped, self-intersecting center vortex loop in SU(2) Quantum Yang-Mills theory we estimate the spatial radius R 0 of this self-intersection region in terms of the electron’s Compton wave length λ C . This region, which is immersed into the confining phase, constitutes a blob of deconfining phase of temperature T 0 mildly above the critical temperature T c carrying a frequently perturbed BPS monopole (with a magnetic-electric dual interpretation of its charge w.r.t. U(1)⊂SU(2)). We also establish a quantitative relation between rest mass m 0 of the electron and SU(2) Yang-Mills scale Λ , which in turn is defined via T c . Surprisingly, R 0 turns out to be comparable to the Bohr radius while the core size of the monopole matches λ C , and the correction to the mass of the electron due to Coulomb energy is about 2%.